Influencer Marketing on The Social Networking Sites and Its Impact On the Dimensions of Customer-Based Brand Equity(CBBE):An Empirical Study on University Students in Yemen - Al-hariry, Khaled (The Arab Journal of Administration, 2019)
This study aimed to identify the main tools that used in marketing of brands through the influencers on the social networking sites, and determine the impact of these tools on the dimensions of The Customer-Based Brand Equity. In order to achieve the aims of the study, researcher adopted the descriptive analytical method and design of a questionnaire to gather preliminary data. The study sample included of (531) individuals from University Students who are the users of social networking sites in Yemen. For testing the study’s hypotheses and data analyzing, many statistical have been used such as regression analysis. The study results showed that The friends, co-workers and sports celebrities were the most influential in the trends and attitudes of customers towards brands on the social networking sites, The results also showed that there is significant impact between the influencer marketing tools for brand on the social networking sites, and the overall dimensions of Customer-Based Brand Equity, the study provide many recommendations to increase the effectiveness of influencer marketing campaign through influencers on the social networking sites, by the business organizations in Yemen.